RELATIONSHIP BETWEEN PREOPERATIVE FOVEAL MICROSTRUCTURE AND VISUAL ACUITY IN MACULA-OFF RHEGMATOGENOUS RETINAL DETACHMENT: Imaging Analysis by Swept Source Optical Coherence Tomography. Issue 10 (October 2020) - Noda, Hiroshi; Kimura, Shuhei; Morizane, Yuki; Toshima, Shinji; Hosokawa, Mio Morizane; Shiode, Yusuke; Doi, Shinichiro; Takahashi, Kosuke; Hosogi, Mika; Fujiwara, Atsushi; Shiraga, Fumio
Abstract : Purpose: To visualize foveal microstructures in macula-off rhegmatogenous retinal detachment using swept source optical coherence tomography preoperatively and postoperatively and to investigate the relationship between foveal microstructures and postoperative visual acuity. Methods: We retrospectively analyzed 42 eyes of 42 consecutive patients diagnosed with macula-off rhegmatogenous retinal detachment who underwent anatomically successful repair surgery and were followed up for 6 months. We used swept source optical coherence tomography to investigate the relationship between preoperative and postoperative continuity of both the external limiting membrane (ELM) and ellipsoid zone (Ez) and preoperative and postoperative best-corrected visual acuity. Results: Both preoperative ELM and Ez were continuous in 9 eyes (21%; ELM+/Ez+ eyes), only the ELM was continuous in 25 eyes (60%; ELM+/Ez− eyes), and neither was continuous in 8 eyes (19%; ELM−/Ez− eyes). Postoperative best-corrected visual acuity in ELM+/Ez+ eyes (−0.05 ± 0.04 logarithm of the minimum angle of resolution units, Snellen equivalent 20/18) was significantly better than that in both ELM+/Ez− (0.16 ± 0.16, 20/29; P = 0.03) and ELM−/Ez− (0.86 ± 0.37, 20/145; P < 0.001) eyes. Postoperative best-corrected visual acuity was significantly better in ELM+/Ez− than in ELM−/Ez− eyes ( P < 0.001). Conclusion: In macula-off rhegmatogenous retinal detachment, preoperative continuity of the ELM and Ez may be a predictor of postoperative best-corrected visual acuity. Abstract : Supplemental Digital Content is Available in the Text.The authors visualized preoperative foveal microstructures of patients with macula-off rhegmatogenous retinal detachment using swept-source optical coherence tomography and found that continuity of the external limiting membrane and ellipsoid zone is a novel prognostic factor for postoperative visual acuity.